THE USE OF ICT IN LEARNING PROCESS BY VOCATIONAL TEACHERS OF ENGLISH - Resty Wiranda; Ismail Petrus; Machdalena Vianty (University of Kuningan, 2020)
In the era of modernization, people are very dependent on technology, Information Communication Technology (ICT) in education itself has important role in teaching and learning process. The purpose of this study was to investigate the kind of ICT used by the teachers, the utilization of ICT in learning process, the problems and solutions in teaching by using ICT, and the role of schools in assisting teachers to overcome the problems at vocational high schools in Sekayu. This study applied descriptive qualitative research design. The data were collected by using questionnaire, interview, observation, and document review. The participants of this study were the teachers of English, the vice-principal of facility and infrastructure, and the students. The findings of this study showed that the teachers of English at vocational high schools in Sekayu used hardware such as projector, laptop, speaker, headset, and smartphone, while software such as internet, dictionary application, e-book, Microsoft office, and browsing application. The teachers used discovery learning to utilize ICT in the syntax of the learning model. The main problem faced by the teacher was the unavailability of students’ personal ICT devices. The school also had the role to assist teachers in overcoming the problems. The conclusion was the teachers had applied ICT in the learning process however they did not fully apply ICT in each syntax of the learning model used.